2021
DOI: 10.1002/mus.27435
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐mediated necrotizing myopathy: Unusual presentations of a treatable disease

Abstract: Introduction/Aims: Immune-mediated necrotizing myopathy (IMNM) is an immunemediated myopathy typically presenting with progressive subacute weakness and characteristic, but nonspecific, myopathological findings. Atypical cases however can mimic other inherited or acquired myopathies, depriving patients of treatment. We describe a cohort of such patients.Methods: We retrospectively identified IMNM patients who either previously carried a diagnosis of an inherited myopathy established on clinicopathological grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…4 These autoantibodies represent an easily accessible means of detecting previously unsuspected cases of IMNM, especially in patients with a young age of onset, chronic course of disease, positive family history without genetically identified etiology, or atypical myopathological findings. 5,6 We found that these atypical presentations represented approximately 5% of IMNM cases in our cohort. It should be noted that the true incidence could be higher, as additional cases may have gone undetected in the absence of serological testing.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…4 These autoantibodies represent an easily accessible means of detecting previously unsuspected cases of IMNM, especially in patients with a young age of onset, chronic course of disease, positive family history without genetically identified etiology, or atypical myopathological findings. 5,6 We found that these atypical presentations represented approximately 5% of IMNM cases in our cohort. It should be noted that the true incidence could be higher, as additional cases may have gone undetected in the absence of serological testing.…”
mentioning
confidence: 59%
“…There are several reports demonstrating that a SARS-CoV-2 infection can be complicated by hypophysitis. 6 Furthermore, patients with a pre-existing pituitary micro-or macroadenoma have an increased risk of pituitary apoplexy during SARS-CoV-2 infection. 7 Accordingly, the hypophysial-pituitary-adrenergic axis can be impaired, 8 thus leading to autonomic dysfunction.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Patients' clinical characteristics are shown in Table 1. Two patients (patients 4 and 5) were described in detail in a previous study 15 . Six patients (patients 1‐6) were tested for IMNM antibodies (four anti‐HMGCR IgG positive, one anti‐SRP IgG positive, and one double seronegative).…”
Section: Resultsmentioning
confidence: 99%
“…Two patients (patients 4 and 5) were described in detail in a previous study. 15 Six patients (patients 1-6) were tested for IMNM antibodies (four anti-HMGCR IgG positive, one anti-SRP IgG positive, and one double seronegative). Two (patients 1 and 6) of the three patients, who were diagnosed with IMNM before IMNM antibody testing became commercially available, were tested on serum…”
Section: Epidemiology and Clinical Serological And Pathological Pheno...mentioning
confidence: 99%
“…We read with interest the clinical research report by Nicolau et al 1 Although we found their article to be stimulating and informative, we believe that the authors' conclusions need to be read with certain caveats, to avoid misinterpretation.…”
Section: Atypical Presentations Of Immune-mediated Necrotizing Myopat...mentioning
confidence: 93%